Assessing land subsidence from anthropogenic activity in Northern Sumatra, Indonesia revealed using SAR interferometry - Perdana, Redho Surya; Anggara, Ongky; Suhadha, Argo Galih; Pangestika, Dita Mulia; Atmojo, Aulia Try; Al Attar, Muhammad Nabil; Sonya, Putri; Alif, Satrio Muhammad (Brawijaya University, 2025)
Land subsidence is a significant issue in urban areas globally, including several cities with a growing population in Northern Sumatra, Indonesia. This study employs Sentinel-1 SAR data and the Small Baseline Subset (SBAS) InSAR technique to monitor land subsidence in Medan, Deli Serdang, Dumai, North Aceh, and Lhokseumawe from 2015 to 2023. The SBAS algorithm was implemented in LiCSBAS with an unwrapped interferogram. Then corrected for atmospheric effects using GACOS, was employed to increase the results of the land subsidence. The analysis was enhanced using GRACE satellite data to assess the impact of groundwater depletion on subsidence. Results indicate significant subsidence across all study regions, particularly in Medan and Dumai, with rates ranging from -48.6 mm/year to +54.1 mm/year. The findings highlight the critical role of rapid urbanization, excessive groundwater extraction, and oil and gas exploration in driving subsidence. This study underscores the need for sustainable urban planning and aquifer management to mitigate future environmental and infrastructural risks.